2020
DOI: 10.3390/microorganisms8111718
|View full text |Cite
|
Sign up to set email alerts
|

New Insights in Laboratory Testing for COVID-19 Patients: Looking for the Role and Predictive Value of Human epididymis secretory protein 4 (HE4) and the Innate Immunity of the Oral Cavity and Respiratory Tract

Abstract: COVID-19 is a viral pandemic caused by the new coronavirus SARS-CoV-2, an enveloped positive stranded RNA virus. The mechanisms of innate immunity, considered as the first line of antiviral defense, is essential towards viruses. A significant role in host defense of the lung, nasal and oral cavities is played by Human epididymis secretory protein 4 (HE4) HE4 has been demonstrated to be serum inflammatory biomarker and to show a role in natural immunity at the level of oral cavity, nasopharynx and respiratory t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 55 publications
4
40
1
3
Order By: Relevance
“…This alteration modifies the composition of the intestinal microbiota both qualitatively and quantitatively. In turn, this influences the gut/pulmonary crosstalk [ 14 , 18 , [21] , [22] , [23] , [24] ].…”
Section: The Sars-covid-19 Action On Microbiotamentioning
confidence: 99%
“…This alteration modifies the composition of the intestinal microbiota both qualitatively and quantitatively. In turn, this influences the gut/pulmonary crosstalk [ 14 , 18 , [21] , [22] , [23] , [24] ].…”
Section: The Sars-covid-19 Action On Microbiotamentioning
confidence: 99%
“…Encephalitis/meningoencephalitis may cause direct damage to the brainstem respiratory center, which may be one of the reasons for the extremely high fatality rate in patients with COVID-19. Detailed biopsy or autopsy neuropathology studies should answer this question[ 59 ]. From the perspective of infectious diseases of the CNS, the cases of SARS-CoV-2-associated encephalitis that were reported lack direct evidence of SARS invading the nervous system, while the cases of COVID-19 patients who were tested for CSF while excluding other potential diagnoses were only accidental reports.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in the USA also observed significant microbiota changes in an adult COVID-19 population [ 114 ]. Several UA immune responses are linked to COVID-19 outcomes, including changes in human epididymis secretory protein 4 [ 163 ]. However, further analysis of COVID-19′s influence on the UA microbiota and the influence of the UA microbiota on COVID-19 severity need further addressing.…”
Section: Limitations and Future Researchmentioning
confidence: 99%